An Overview of Problems Concerning Political Donations in Japan - Misawa, Mitsuru (Columbia Journal of Asian Law, 2008)
In Japan, there has been increased scrutiny of companies’ general participation in the political process, in particular political campaign contributions. Over the past decade, Japan has placed new restrictions on companies’ political giving and has required greater disclosure of campaign contributions. Increasingly, shareholders are seeking to hold companies accountable for their campaign contributions. However, political activities generally require substantial funds and the situation in Japan is no different. Consequently, political activities require donations from corporations and individuals. In Japan the challenge to the ruling Liberal Democrats, and the broader political crisis, in the 1990s and early 2000s centered on a series of scandals involving payments to politicians for their huge election expenses. Political donations are classified by donor into two groups: corporate donations and personal donations. Under current law, corporate donations are often viewed as collusion between business entities and politicians. Therefore, donations to individual politicians are prohibited, unless the donation is to a single fund raising group managed by a particular politician. An individual politician can appoint only one organization as a single fund managing organization through which he can accept political donations from individuals. This exception is applicable only to personal donations. Donations to political parties can be divided into two categories: (1) those made directly to political parties; and, (2) those made to political funding organizations controlled by political parties. Corporations and individuals may donate money to either institution. However there is a limit on the political donations of corporations: corporations that have lost money over three consecutive years cannot make any political donations. Political donations made under such adverse circumstances may be considered to have unhealthy and unsound purposes; further, shareholders may not approve of such contributions.